1980
DOI: 10.1530/jrf.0.0590311
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizing ability of semen from rams of high- and low-prolificacy flocks

Abstract: The difference between fresh undiluted ram semen from high (H) and low (L) prolificacy Romney selection lines in success in fertilizing artificially inseminated Romney, half-Romney and Cheviot ewes (unrelated and randomly allocated) was examined in 3 experiments. For ewes producing natural multiple ovulations, the fertilization rate was 71% (40/56) and 40% (20/50) for semen from H rams and L rams respectively (P < 0.01). Fertilization rates for PMSG-induced multiple-ovulating ewes were 61% (11/18) for H semen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Increased sizes in these highly androgen-sensitive tissues suggest a pattern of greater functional activity in polygynous males. The epididymal sperm counts indicate that short-term physiologic activation may elevate fertility also (24,36).…”
Section: Discussionmentioning
confidence: 99%
“…Increased sizes in these highly androgen-sensitive tissues suggest a pattern of greater functional activity in polygynous males. The epididymal sperm counts indicate that short-term physiologic activation may elevate fertility also (24,36).…”
Section: Discussionmentioning
confidence: 99%
“…CLARKE (1978) concluded from these results that there has been little associated response in the ewes' contribution to fertility from selection for or against twinning frequency but very much in the ability of the ram to get ewes in lamb. This suggestion has later been verified by MOORE and WHYMAN (1980) who found an enhanced fertilization rate of semen from Ruakura high line rams, particularly in ewes with multiple ovulations (71 and 40% respectively). The same authors found also an improved paternal component in the sheep screened for fecundity in the Waihora sheep improvement programme.…”
Section: Some Evidence For Non-maternal Effects From the Literaturementioning
confidence: 61%